PENGARUH KOMUNIKASI, PERSEPSI DUKUNGAN ORGANISASI DAN KEPRIBADIAN (PERSONALITY) TERHADAP KINERJA GURU SMP NEGERI 3 MANDOR KABUPATEN LANDAK - Mujiono (JURNAL ILMIAH EDUKATIF, 2019)
This study aims to know and analyze (1) communication, perception of organizational support, personality and performance, (2) communication effect, perception of organizational support and personality toward teacher performance of SMP Negeri 3 Mandor Kabupaten Landak. Population in this research is teacher of SMP Negeri 3 Mandor Regency Landak with population amount 35 people and all become sample. Data analysis technique used isregression model. The results showed that communication variables, perception of organizational support, personality (personality) and teacher performance of SMP Negeri 3 Mandor Kabupaten Landak showed general results included in good criteria. The result of regression model test shows that the influence of communication, perception of organizational support, personality (personality) toward the performance of SMP Negeri 3 Mandor Kabupaten Landak significant.